La Dysorthographie A L’épreuve De L’environnement Social. Une Analyse Chez Des Élèves A L’école Primaire Ivoirienne - Arsene, Seka Yapi (European Scientific Journal, ESJ, 2017)
The article analyzes the impact of environmental determinants on spelling in learners at the preparatory elementary school. It shows how spelling in learners can be influenced by environmental factors causing dysorthographia. The aim of the study is to analyze the effect of the social environment on students’ written productions by showing more specifically that orthographic distortions depend to a large extent on the quality of the social environment. The survey is being carried out in preparation for primary school (CP1) in three departments of Côte d’Ivoire. Evaluations are proposed to process data from the chi-square. The quantitative method is preferred and the experimental approach makes it possible to conclude that disadvantaged environments favor dysorthographia more in learners.